Correlates of Risky Alcohol and Methamphetamine Use among Currently Homeless Male Parolees - Salem, Benissa E. (2013)
Homeless men on parole are a hard-to-reach population with significant community reintegration challenges. This cross-sectional study describes socio-demographic, cognitive, psychosocial and drug-related correlates of alcohol and methamphetamine use in 157 homeless male parolees (age range 18–60) enrolled in a substance abuse treatment center in Los Angeles. Logistic regression results revealed that being African American and older were negatively related to methamphetamine use, while being older and more hostile were related to riskier alcohol abuse. Findings from this study provide a greater understanding of correlates of methamphetamine and alcohol- two of the most detrimental forms of substances abused among currently homeless parolees.